Efek Merokok Berat terhadap Jumlah Leukosit dan Jenis Leukosit pada Pria Usia Produktif di Kelurahan Tanjung Pinang Kota Palangka Raya - Rinny Ardina; Nada Soraya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Prevalence of productive men smokers in Kalimantan Tengah in 2013 has been reached 64.9% with a mean of smoking about 12.3 cigarettes a day. Cigarette smoke contains 1015 of oxidative free radicals which can cause oxidative stress. It will trigger of activation of inflammatory genes and increase of cytokines release by increasing of leukocytes and activate some of the differential leukocytes. Continual inflammation can cause atherosclerosis and coronary heart disease. This study aimed to determine the effects of heavy smoking on white blood cell count and differential leukocyte count in productive men in Kelurahan Tanjung Pinang, Palangka Raya. This study used a descriptive observational method with a cross-sectional design. The sample obtained by 28 people with purposive sampling technique with criteria: men, active smoker, smoking more than ten years, working as a farmer, fish farmer, or laborer, and willing to become a respondent. White blood cell count and differential leukocyte count were analyzed by an automatic method using Hematology Analyzer. The results showed that 3.6% of active smokers had high white blood cell count and others had low white blood cell count (3.6% ). Whereas differential leukocyte count showed that 2 persons had high of eosinophils (7.10%), 5 people had low of eosinophils (17.9%), one person had little of neutrophils (3.6%), 2 persons had high of lymphocytes (7.20%), 10 people had little of lymphocytes (35.7%), and 15 people had high of monocytes (53.6%). To reduce the risks, preventive and educative actions from medical personnel are needed for active smokers and their families.